65.1k views
4 votes
(2x + 1 ) (x - 3 ) = 2x² - 5x -3

Is it correct ? please I need all the way that allows us to have this answer

User Shaneice
by
5.2k points

2 Answers

5 votes

Answer:

YES. It is correct.

Explanation:

Use FOIL:

(a + b)(c + d) = ac + ad+ bc+ bd

(2x + 1)(x - 3)

= (2x)(x) + (2x)(-3) + (1)(x) + (1)(-3)

= 2x² - 6x + x - 3 combine like terms

= 2x² + (-6x + x) - 3

= 2x² - 5x - 3

User Dhruv Raval
by
6.0k points
4 votes

Answer:

It is.

Explanation:

1. Multiply 2x *x and 2x* -3 ;

2. Multiply 1*x and 1*(-3) ;

You should get: 2x^2 -6x +x -3 = 2x^2 -5x -3;

3. Add -6x +x;

In the end you get : 2x^2 -5x -3=2x^2 -5x -3

User Albaregar
by
5.9k points